Anomie in the Complex Socium - N. N. Mescheryakova (Vestnik MGIMO-Universiteta)
The article deals with the question of what changes should be made in the theory of social anomie, formulated by Emile Durkheim and developed by Robert Merton. This is necessary because modern society has entered a qualitatively new stage in its development and is characterized by the notion of a complex socium. Anomie in a simple socium can be defined as structural. Social system itself creates the conditions in which the destructive behavior is "normal" response to the social situation. Anomie of modern complex society can be defined as reflexive. Variety of value-normative systems leads to the fact that norms become an act of choice. Decision-making center has shifted to the level of the microcosm. They have become as unpredictable as social life in general.